2008
DOI: 10.1007/s10517-008-0233-0
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal hyperhomocysteinemia as a model of oxidative stress of the brain

Abstract: We found that methionine added to the ration of pregnant rats (1 g/kg body weight) induced sustained hyperhomocysteinemia and led to the formation of sustained oxidative stress in the brain of their progeny. Newborn animals were characterized by lower body weight, SOD deficiency in the brain, increased neuronal death, and desensitization of NMDA receptors. These factors are associated with impaired cognitive capacity in the Morris test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 8 publications
1
22
0
Order By: Relevance
“…Some reports suggested that hyperhomocysteinaemia causes oxidative stress in different tissues in adult mammals (Mujumdar et al 2001;Wang et al 2004;Makhro et al 2008;Sema et al 2010). It was hypothesised that increased lipid peroxidation levels might be an important risk factor for this (Sema et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Some reports suggested that hyperhomocysteinaemia causes oxidative stress in different tissues in adult mammals (Mujumdar et al 2001;Wang et al 2004;Makhro et al 2008;Sema et al 2010). It was hypothesised that increased lipid peroxidation levels might be an important risk factor for this (Sema et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Homocysteinuria is a metabolic disorder characterized by deficiency of the enzyme cystathione bsynthase activity leading to accumulation of homocysteine. Homocysteine causes free radical formation and severe neurological dysfunction, which is thought to be due to the increased oxidative stress (263). Administration of homocysteine to adult rats caused severe memory impairments in the stepdown inhibitory avoidance test that was prevented by pretreatment with vitamins C and E, suggesting that ROS play a critical role in the onset of memory dysfunction during homocysteinuria (358).…”
Section: Ros In Multiple Disease Statesmentioning
confidence: 99%
“…Moreover, other factors may also exert important effects, such as oxidative stress [14], [15], exercise [16] and epigenetic modifications [5].…”
Section: Introductionmentioning
confidence: 99%